Feeling of burden and social support in family caregivers of chronically ill patients - Seidmann, Susana (2004)
We evaluate if the social network structure, the percei ved support and the personal satisfaction acts on the caregiver's feeling of burden, coming from the caring of a child oran older parent with chronic invalidating illness. We used Mannheim's Instrument for Social Support (1986) and the Feeling of Burden Questionnaire (Zarit & Zarit, 1999) with 143 caregivers -50,3% mothers and 49,7% daughters. Taking into account the multivariate statistical tests, we can conclude that mothers have a larger relatives network than daughters, even though they don't significantly differ in the perception of social support. In mothers, the size of the relatives network, the everyday instrumental and the psychological crisis support diminishes the feeling of burden, as for the daughters the more intense crisis instrumental perceived support diminishes the same feeling.